Science smart workbook 6 (Singapore : Alston Publishing House, 2012)
Science Smart series is developed to cover comprehensively the learning outcomes of the latest Cambridge Primary curriculum framework. Adopting the Inquiry Approach, Science Smart uses engaging visuals and presentation formats with well-crafted activities to arouse pupils' curiosity about the world around them. This motivates pupils to learn, enabling them to better grasp key scientific concepts. At the same time, emphasis is given on developing pupils' inquiry and process skills, critical thinking, as well as 21st Century skills. Science Smart also develops pupils' exam confidence. Exam-style questions are provided at the end of every chapter, with hints and helping questions to guide pupils' thought processes. This prepares pupils well for the Cambridge Primary Checkpoint tests.
Keywords: Science--Study and teaching